Depresión en los adultos mayores asilados en la casa hogar Betania de la ciudad de Zamora. Año 2015 - Gualán Chalán, Claudia Alejandrina (2016)
This study was aimed to investigate depression in the elderly refugees in Bethany Home town house of Zamora. 2015, the methodology that the author used was cross, descriptive, bibliographical, prospective field type. To comply with this study, interview technique is applied with the questionnaire instruments and test Geriatric Depression Yesavage, the same as were applied to 34 elderly resulting in the following: in relation to the general characteristics it was found that 58.82% are male, aged between 75-90 years with 44.12% of mixed ethnicity with 91,17%, from urban and rural with 50% of primary level with 61.76%, and currently not engaged in any trade or activity with 97.06%. On the level of depression could be identified 44.12% of seniors without depression, 47.06% had mild depression and 8.82% severe depression. The triggers of depression are the economic level, the death of a loved one and physical illness or chronic degenerative with 55.88% each, the consumption of drugs 50.00%, moving to 47,05%, marital status divorced with 5.88% and finally the use of psychoactive substances such as cigarette with 2.94%. Why an intervention plan based nursing occupational, recreational, educational and health activities aimed at the elderly, the staff of the children's home and family, thereby concluding that there is depression in the elderly is implemented and clear symptoms are sadness, loneliness and low self esteem. Keywords. Depression, Elderly, Asylum